Biodiversity Loss Threatens Human Well-Being - Díaz, Sandra; Fargione, Joseph; Chapin, F. Stuart; Tilman, David (PLoS biology, 2006)
At least among species within the same trophic level (e.g., plants), rarer species are likely to have small effects at any given point in time. [...]in natural systems, if we are to preserve the services that ecosystems provide to humans, we should focus on preserving or restoring their biotic integrity in terms of species composition, relative abundance, functional organization, and species numbers (whether inherently species-poor or species-rich), rather than on simply maximizing the number of species present.\n Ecosystem services are the benefits provided by ecosystems that contribute to making human life both possible and worth living. [...]the service of formation, retention, and sustained fertility of soils necessary for the production of plants and animals considered important by different human societies depends on the ecosystem processes of decomposition, nutrient cycling by soil microbiota, and the retention of water and soil particles by a well-developed root network (Figure 1, path 2 and top sub-box in red of Ecosystem Services box).